Efektivitas Pembelajaran Afeksi di Madrasah/Sekolah - Ainul Yaqin (Islamica: Jurnal Studi Keislaman, 2011)
A nation will be destructed if it suffers from moral decadence. A society would decline if it does not have good character. Hence, the need to raise the awareness of the people concerning the importance of morality and good character. This paper is part of that movement to raise the importance of moral virtue. It speaks of morality as a form of mental attitude and personality. The paper moves to explore the central role that Madrasah/School can play as a strategic partner toward this end. The paper discovers that thus far the Madrasah and schools in the country are indulging only in the cognitive aspect of the students, ignoring in the process their affective and spiritual aspects. The last two are processes toward character building, leaving them aside will lead to moral loses. The paper finally offers some conceptual and practical steps in which educating students affectively and spiritually can be done.